Factors Causing Non-Adherence to Lifestyle Modification in type II Diabetes Patients: A Cross-Sectional Study - Mansoor Ul Haque, Nazia Hussain, Khuda Bux, Mushtaque Ahmed, Asif Ali Thebo, Khushboo Chandio (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the factors causing non-adherence to lifestyle modification in type II diabetes patients. Study design: A cross-sectional study Place and Duration: This study was conducted at Global Institute of Medical and Health Sciences Hyderabad Pakistan from June 2020 to June 2021 Methodology: The study included 374 individuals who were more than 20 years of age and had type II diabetes for more than 1 year. Different factors which might have an association with non-adherent behavior to lifestyle modification were assessed. The results were statistically analyzed using SPSS version 23. Results: It was observed that 88% of patients were non-adherent towards diet, 25% were towards exercises, 70% towards foot care, 6% towards smoking, and 25% towards skipping the betel quid chewing even after being instructed by the health care workers. Conclusion: Nonadherence towards lifestyle modification is quite challenging to achieve a healthy and stable lifestyle in diabetic patients. So such studies must be conducted on a larger scale to develop proper interventions.